Analisis Peran Seksi Penyelenggara Syariah Dalam Pengumpulan Zakat Profesi ASN di Lingkungan Kantor Kementerian Agama Kota Medan - Dinda Melani Putri; Zuhrina M. Nawawi (LPPM IAI Nasional Laa Roiba Bogor, 2022)
Every muslim wants to echieve perfection in worship by carrying out all the commands of Allah SWT and staying away from all his prohibilitions. The pilliars of Islam and the pilliars of faith are guidelines for muslims to become true Muslims. There are five pilliars, islam and paying zakat is an obligation that must be issued by someone who has excess assets. Profesional zakat is part of zakat maal which must be issued on essest derived from regular income work that does not violate islamic law. Baznas after entrusting to the agency or company to collect zakat for its employees. The perpose of this study is to find out how the role of the islamic organizer section in collecting professional zakat is in the office of the ministry of religion in the city of Medan. The main problem related to this research is the effort and role of the islamic organizer section in collecting professional zakat. The object of this research is the islamic organizer secton of the Medan city ministry of religion. Keywords : Professional Zakat, Collection, Syariah administration section.